Electrical stimulation to improve meat quality: Factors at interplay, underlying biochemical mechanisms and a second look into the molecular pathways using proteomics - Gagaoua, Mohammed; Prieto, Nuria; Hopkins, David L.; Baldassini, Welder [UNESP]; Zhang, Yimin; López-Campos, Oscar; Albenzio, Marzia; della Malva, Antonella (Elsevier, 2025)
Ensuring consistent beef eating quality is paramount for meeting consumer demands and sustaining the meat industry. Electrical stimulation (ES) is a post-slaughter intervention used to accelerate post-mortem glycolysis, to avoid cold shortening, to control the tenderization rate of meat through sophisticated physical, chemical and biochemical mechanisms including proteolysis, to improve beef tenderness and to achieve normal pHu that might lead to positive impact on color. This review comprehensively examines the multifaceted effects of ES on beef quality, encompassing factors and settings influencing its efficacy and the underlying biochemical mechanisms revealed using traditional biochemistry methods. It then delves into the molecular pathways modulated by ES, as unveiled by muscle proteomics, aiming to provide a second look and an unprecedented understanding of the underlying biochemical mechanisms through an integrative proteomics analysis of low-voltage ES (LVES) proteomics studies. The proteins changing as a result of ES were gathered in a compendium of 67 proteins, from which 14 were commonly identified across studies. In-depth bioinformatics of this compendium allowed a comprehensive overview of the molecular signatures and interacting biochemical pathways behind electrically stimulated beef muscles. The proteins belong to interconnected molecular pathways including the ATP metabolic process and glycolysis, muscle structure and contraction, heat shock proteins, oxidative stress, proteolysis and apoptosis. Understanding the intricate interplay of molecular pathways behind ES could improve the efficiency of beef production, ensuring consistent meat quality and meeting consumer expectations. The integrative analysis approach performed in this study holds promise for the meat industry's sustainability and competitiveness.
Keywords: Bioinformatics; Biological pathways; Electrically stimulated muscle; Glycolysis; LVES; Muscle proteome; Muscle structure; Programmed cell death; Small heat shock proteins